Matrix Function for Solving Optimal Game Pass Strategy Summary - Qinling Zhao; Xiangdan Wen (International Journal of Engineering and Management Research, 2020)
The breakthrough is to quantify the amount of water, food and money carried by people in the desert and to construct a discrete function with the number of days as a time variable, optimal Planning and design for the outflow of desert-walking resources and the introduction of resources and funds from the starting point, villages and mining areas, these resources and funds are fitted by the Adjacency Matrix and the coherent knowledge of probability to describe their dynamic changes with time (days). According to the restriction of the rules of the game, we try to find the optimal solution by computer software (Matlab) in order to reduce the computation of human brain.